Rancang Bangun Mesin CNC Menggambar Berbasis Arduino dengan Inkscape dan GRBL - Irdan Guntara; Ragel Trisudarmo; Kiki Amalia Sapitri; Dea Yulistiana Dewi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research successfully designed and built a CNC drawing machine based on Arduino. The system utilizes NEMA stepper motors to move the X and Y axes, as well as a servo motor to control the Z axis. The Arduino Uno, supported by GRBL firmware, acts as the central controller that processes commands from the Inkscape software. The results of the research demonstrate that the developed CNC machine is capable of producing images with satisfactory accuracy. The appropriate selection of components and optimal parameter settings have contributed to the machine's reliable performance.